How social networks promote brand activism and the importance of authenticity in achieving results - Miguel, A.; Miranda, S. (Inclusión y activismo digital: participación ciudadana y empoderamiento desde la diversidad, 2021)
The use of the Web on a global scale and based on two-way communication, provided by Web 2.0, enabled the creation and dissemination of social movements and online activist practices, due to the greater ease and reach of the association of individuals in “virtual communities”, characterized by shared interests and common issues. In addition, the access to additional sources of information on the Web and the greater ability of the masses to make their opinions heard, has balanced the distribution of power, allowing an increasingly closer and interactive relationship between audiences and social organisms, like companies. In the field of online communication between brands and consumers, social networks play a prominent role as a stage for this new ability for public influence and participation. The public, increasingly aware of the most varied socio-political problems, quickly began to approach brands on social platforms as a way to pressure companies to adopt a more active role in society and to comment on relevant social and political issues. Some even join in “anti-brand movements” or in “anti-brand communities” when considered that brands reveal an irresponsible position regarding the consequences of their activities and/or a communication that doesn’t suit the values defended by consumers. From this closer communication, brands began to become aware of the need to commit themselves to the demands of consumer-activists and to get involved in the causes of society itself, beginning to take a public position on the most pressing and current social, political, economic and/or environmental issues, initiating the so-called Brand Activism. However, there are several factors influencing adherence of brands to activism and the outcomes of such actions, like the possibility and ease of access of companies and consumers to the Information Age and mainly the authenticity demonstrated by brands when defending a certain cause, complementing online actions with offline activist practices. This gave rise to positive, negative and neutral theories about the impact and effectiveness of digital activism. This theoretical investigation will thus contribute to expose and discuss the factors that made social networks a dual platform, which, on the one hand, presents itself as a lever for the emergence and proliferation of Brand Activism and, on the other hand, is today one of the most important means for brands to develop actions to fight for positive socio-political changes. Based on a bibliographic review and concrete examples of brands that are already involved in activism actions, a current picture of the application of this concept will be presented, as well as the different perspectives that guide the area. In addition, conclusions will be presented on the constraints to the practices of brand activism around the globe, derived from the unequal access and use of technology and the economic, social and political context in which the use of the technology occurs. Finally, the importance of authenticity for obtaining favorable results will be explained, namely in terms of coherence between the communication carried out by brand on its various platforms and its values and offline practices regarding the same subjects.